Dramma Giocoso : four contemporary perspectives on the Mozart/Da Ponte operas - Rushton, Julian ([Leuven] : Leuven University Press, 2012)
In exploring the evergreen qualities of Don Giovanni and Le Nozze di Figaro, this collection of studies does not shun approaches that have foundations in established theory, but refracts them through such problems as the tension between operatic tradition and psychological realism, the co-existence of multiple yet equal plots, and the antagonism between the tenets of tradition and the need for self-actualization. In exploring such themes, the authors not only illuminate new aspects of Mozart's operatic compositions, but also probe the nature of musical analysis itself.
'By their arias shall ye know them' : characterization in aria-based opera / Julian Rushton -- Don Ottavio and the history of the tenor voice / Stefan Rohringer -- Don Giovanni then and now : text and performance / Sergio Durante -- The Act IV finale of Le nozze di Figaro : dramatic and musical construction / James Webster.
Includes bibliographical references.
Keywords: Mozart, Wolfgang Amadeus, -- 1756-1791 -- Criticism and interpretation; Da Ponte, Lorenzo, -- 1749-1838 -- Criticism and interpretation; Opera; Musical analysis; Muzika boterore - Teoria e muzikes - Kritika - Interpretimi -- Muzika boterore - Teoria e muzikes - Analiza muzikore - Opera -- Muzika boterore - Teoria e muzikes - Mozart - Kritika - interpretimi -- Muzika boterore - Teoria e muzikes - De Ponte - Kritika - interpretimi